Analisis Kebijakan Fiskal Dalam Mengatasi Kemiskinan Melalui Pemberdayaan Dana Desa: Kajian Literatur - Adzam, Muh; Hanna Usnitayati; Afrian Arga Prastya; Naufal Afaf Bernantus; Alfarid S. Lamora (Public Service and Governance Journal, 2024)
This paper discusses the role of fiscal policy in overcoming poverty in Indonesia through empowering village funds. Using a literature study approach, the data collection process uses secondary data from the Central Statistics Agency and the Ministry of Finance. This paper examines poverty analysis, factors that influence poverty, and the implementation of fiscal policy in reducing poverty levels. Apart from that, this research also discusses village fund empowerment policies, poverty alleviation strategies and implementation of village fund policies. The research results show that fiscal policy, especially increasing village fund allocation, can be effective in reducing poverty. Programs such as empowering village funds can improve community welfare and reduce poverty levels. Evaluation of the village fund empowerment policy shows a positive impact on poverty alleviation, with increasing village status and reducing poverty levels in rural areas. And by involving the community to participate in managing village funds so that the implementation of village funds can be achieved.